Coronavirus Research Database
Including coverage of the COVID-19 outbreak, this database curates openly available content related to coronaviruses. It will continue to grow and evolve as more is learned about the pandemic. The Coronavirus Research Database saves time and improves outcomes for researchers by aggregating authoritative content from ProQuest with content made available at no cost by members of the International Association of STM Publishers – including Springer Nature, Taylor & Francis and The BMJ. Journals, preprints, conference proceedings and dissertations provide comprehensive coverage of COVID-19 and other past coronavirus outbreaks, such as MERS and SARS, for context around the current global pandemic. Full-text content in the database is available either directly from ProQuest or via links to publisher sites.